Estimating the relation between digitalization and the market value of insurers - Simon Fritzsch; Philipp Scharner; Gregor Weiß (Journal of Risk and Insurance, 2021)
We analyze the relation between digitalization and the market value of US insurance companies. To create a text-based measure that captures the extent to which insurers digitalize, we apply an unsupervised machine learning algorithm—Latent Dirichlet Allocation—to their annual reports. We show that an increase in digitalization is associated with an increase in market valuations in the insurance sector. In detail, capital market participants seem to reward digitalization efforts of an insurer in the form of higher absolute market capitalizations and market-to-book ratios. Additionally, we provide evidence that the positive relation between digitalization and market valuations is robust to sentiment in the annual reports and the choice of the reference document on digitalization, both being issues of particular importance in text-based analyses.
Keywords: 330; digitalization; Latent Dirichlet Allocation; machine learning; market valuation